KEPEMIMPINAN GURU DALAM PEMBELAJARAN DI ERA DIGITAL - Bilhuda, Asra; Gistituati, Nuhizrah; Rusdinal, Rusdinal; Anisah, Anisah (Jurnal Manajemen Pendidikan, 2025)
The purpose of this study was to determine how teachers direct students in learning activities in the digital era and to determine the impact of the digital era on learning and teachers. This study is a descriptive qualitative study with observation and interview data collection techniques. The use of digital media such as Google Form, Google Classroom, PowerPoint, various learning applications, bloggers, quizizz, Google Meet video conferences, and Zoom meetings have been widely used by teachers. The digital era has positive and negative impacts on the implementation of learning and for teachers. The positive impacts are (1) digital media makes it easier for students to access each learning material; (2) students enjoy digital learning media more; (3) teachers participate in various training to improve their skills; and (4) teachers will continue to learn new things. The negative impacts that arise are (1) learning materials become broader so that essential materials are not obtained; (2) learning is less focused; (3) teachers are not always able to control students one by one in using gadgets; and (4) the enthusiasm and abilities of senior teachers still need to be improved. The conclusion is that teachers as student leaders in learning are expected to be able to package developments in the digital era effectively to facilitate the implementation of learning.